Penerapan Model Pembelajaran Sinektik Menggunakan Media Pembelajaran GeoGebra pada Materi Dimensi Tiga - sunyoto sunyoto (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2020)
This study aims: to determine the improvement of student learning outcomes in three dimensions subject through the application of synectic learning models using GeoGebra learning media. This research is a classroom action research. Which consists of two cycles. The subjects are class XII_IPA students, odd semester 2019/2020 SMA Negeri 1 Kediri. In cycle 1 it is discussed about the distance of two points, the distance of points to a line and the distance of two lines, and in cycle two it is discussed about the distance of points to fields, distance of lines to fields and distance of two fields. The results of the study in cycle 1, obtained an average value of 78,75, completeness 81,25%. As for cycle 2, the average value of 75 completeness is 75%. It can be seen from cycle 1 to cycle 2 that the result is down due to the very complex cycle 2 material, the difficulty level is indeed different. The student response was very positive, student activity increased. Although classical completeness has not been achieved, the results for researchers are very satisfying. Because the mistakes made by some students are not due to the ability to understand, but the lack of accuracy due to nervousness. The application of the synectic learning model by using GeoGebra learning media on the three dimensional material concluded can improve student learning outcomes, and students respond well.